Asymetryczna koncentracja technologii w strukturach sieciowych - Perechuda, Kazimierz (The Assymetric Concentration of the Technology in the Net Structures, 2005)
In the paper are presented:- the role of the dissymmetry in the modem economy,- the essence of the structured net,- the functions of the "integrator company" in the net enterprise,- the assymetrical flow of the new technology in the international net companies,- threats of the assymetrical diffusion of the new technology in the net organizations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 140-146